Absorption, metabolism and bioavailability of flavonoids: a review. Issue 28 (3rd October 2022) - Chen, Lei; Cao, Hui; Huang, Qun; Xiao, Jianbo; Teng, Hui
Abstract: Flavonoids are stored in various plants and widely presented in different kinds of food in variable amounts. Plant roots, stems, leaves, flowers and fruits are known to have high amounts of flavonoids. However, flavonoid aglycones are found less frequently in natural products, as it requires bioconversion through bacteria, which provide β-glucosidase to convert them. Recently, flavonoids and its metabolites were applied in the prevention and treatment of various diseases such as cancers, obesity, diabetes, hypertension, hyperlipidemia, cardiovascular diseases, neurological disorders and osteoporosis in numerous studies. This review focused on absorption, activity, metabolism, and bioavailability of flavonoids. Also authors organized and collected newly-found reports of flavonoids and their absorption barriers of flavonoids in the gastrointestinal tract, providing the latest findings and evidence from the past decade. Particularly, nanoparticles delivery systems are emphasized regarding fabrication methods and their potential benefits on flavonoids. Moreover, the potential challenges of nanoparticles as delivery system for flavonoids in the gastrointestinal tract are also discussed.